THE HISTORY OF LIBRARIES - Toshtemirova Sevinch (International Journal of Literature and Language Studies, 2026)
This paper discusses the origin of libraries, the stages of their historical development, the condition of libraries in ancient and medieval times, and the role of modern libraries in society. It also analyzes the contribution of libraries to the development of science, education, and culture.